Potential for Cripto-1 in defining stem cell-like characteristics in human malignant melanoma - Strizzi, Luigi (2008)
The diagnosis of melanoma is becoming ever more frequent. Although surgical excision of early lesions is associated with relatively significant high cure rates, treatment modalities are largely unsuccessful for advanced disease. Characteristics such as cellular heterogeneity and plasticity, expression of certain molecules such as the multidrug resistance protein-1 (MDR1) or the aberrant expression of embryonic signaling molecules and morphogens like Nodal, important for self renewal and pluripotency, suggest that a stem cell-like population may reside in aggressive melanomas. This perspective focuses on preliminary findings obtained in our laboratory which indicate that the expression of the Nodal co-receptor, Cripto-1, in a subset of malignant melanoma cells may be exploited to identify possible melanoma stem cells (MSC). In fact, the use of anti-Cripto-1 antibodies to cell sort Cripto-1-positive cells in the metastatic melanoma cell line C8161 has identified a slow growing, sphere forming subpopulation that expresses increased levels of Oct4, Nanog and MDR1. If current in vivo studies confirm the self renewal and tumorigenic characteristics of these cells, the expression of Cripto-1 may represent a useful marker to identify cancer stem cells in melanoma, and possibly other aggressive tumors as well.